La Medicina del Lavoro: 100 volumi / La Medicina del Lavoro: 100 volumes - Zocchetti, C. (La Medicina del Lavoro, 2009)
La Medicina del Lavoro: 100 VolumesWith these pages La Medicina del Lavoro starts its 100th volume, so we have yet another historical occasion to celebrate the oldest occupational health journal in the world that is still publishing. Over the last few years we have had many occasions to celebrate, for example several anniversaries of the Journal (the 80th volume in 1989, 90 years in 1992, 100 years in 2001); the centenary of the foundation of the Clinica del Lavoro “Luigi Devoto” of Milan in 2001; the celebration of the 300 years’ anniversary of the publication of De Morbis Artificum Diatriba by Bernardino Ramazzini, and we obviously hope to continue for many years to come in this positive outlook. One hundred volumes makes for a very large collection, with the highs and lows of the Journal’s history (here we mean the variations in number of pages and physical size of the Journal). It is thanks to the Editors-in-chief (there have been very few so we can cite them all: Luigi Devoto, 1901-1936; Luigi Preti, 1936-1941; Enrico Vigliani, 1943-1992; e Vito Foà, 1992 to the present); the contributors who in various ways and with varying degrees of commitment but always with an exceptional personal participation, that it has been possible to reach 100 volumes, starting with C. Moreschi who, along with Luigi Devoto, was the first and sole editor at the Journal’s foundation; up to the present extended and impressive editorial board; the printers (from the first: Tipografia Cooperativa, Via dei Molini in Pavia, to the latest: Casa Editrice Mattioli in Fidenza); the sponsors, including the most evident who, via advertising (rather limited as a matter of fact), directly gave information about themselves, but also those who have often been or are  behind the scenes, ensuring fundamental support which is not visible; content: articles, news, events, reports, ideas, opinions, photographs, tables, numbers…etc, which are really impossible to sum up. But the true collection which, for obvious reasons, cannot be individually named, consists of the people and the ideas that have enriched the history of the Journal in its over 100 years of existence. And the subscribers, above all, who by their almost anonymous presence have been the true guarantors of the Journal’s life. And of course the contributors who with their articles have consigned a part of their lives to history. Starting from 1925 we counted nearly 11.000, a really grand number. It would be wonderful if we could invite them all to a hypothetical (and impossible) grand convention to simply say “Thank you, your contributions will not be forgotten”. There have been 100 volumes but in actual fact the Journal is more than 100 years old. It was founded in Pavia in 1901 as Il Lavoro – Rivista di fisiologia, clinica ed igiene del lavoro, and between 1901 and 1910 only three volumes were published, then, due to the difficulties during the First World War and the immediate post-war years, there were no issues  in 1916, 1918  and 1919. Issues finally became regular in 1920 with volume 11; from that moment on not one issue was missed and the Journal even got through the Second World War without interruptions. In 1925, with volume 16, it took on the name that still distinguishes it to-day: La Medicina del Lavoro, “the official standard bearer of a work of enormous scientific, social and political content” as Luigi Devoto presented the event at the time. The first few years of the Journal were difficult ones (with only three volumes published in 10 years) to the effect that events such as the First International Congress on Occupational Diseases (Milano, 1906), the foundation of the International Commission for Occupational Health (1906), the First National Italian Congress on Occupational Diseases (Palermo, 1907), and above all the inauguration of the Clinica del Lavoro in Milano (20 March, 1910) are not reported in the Journal, which by 1911 hade resumed publication but had moved to Milan. Many years have passed since those first three volumes and in the meantime we have moved on to another century and another millenium: this brings new opportunities, new responsibilities, new perspectives, new objectives, but also new subscribers, new contributors, new authors, and new topics. We would like to conclude by repeating the undertaking made “20 volumes ago”: The Editorial Board wishes to thank everyone and take the opportunity to renew our unfaltering commitment to work well by ensuring our full respect for authors and readers so as to contribute, via the pages of La Medicina del Lavoro, to spreading love and knowledge of our discipline. This number includes the Italian translation, with the original Latin version opposite, of dr. John Darwall’s doctoral thesis discussed at the university of Edinburgh in 1821.